2007
DOI: 10.1145/1243401.1243405
|View full text |Cite
|
Sign up to set email alerts
|

Fairness and classifications

Abstract: The growing trend in computer systems towards using scheduling policies that prioritize jobs with small service requirements has resulted in a new focus on the fairness of such policies. In particular, researchers have been interested in whether prioritizing small job sizes results in large jobs being treated "unfairly." However, fairness is an amorphous concept and thus difficult to define and study. This article provides a short survey of recent work in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Finally, since unfairness is always a worry when using policies based on SRPT scheduling, we provide a study of unfairness under MaxSRPT and SplitSRPT. Similarly to the analysis of SRPT in a single server queue [11,12,26,[34][35][36], our results highlight that unfairness is not a major worry under these policies.…”
Section: Summary Of Contributionssupporting
confidence: 72%
See 2 more Smart Citations
“…Finally, since unfairness is always a worry when using policies based on SRPT scheduling, we provide a study of unfairness under MaxSRPT and SplitSRPT. Similarly to the analysis of SRPT in a single server queue [11,12,26,[34][35][36], our results highlight that unfairness is not a major worry under these policies.…”
Section: Summary Of Contributionssupporting
confidence: 72%
“…In the context of a single server queue, the unfairness of SRPT has received significant attention, e.g., [11,12,[34][35][36]. These studies have revealed that, in practical settings, large jobs actually receive as good (and sometimes better) performance under SRPT as they do under a fair scheduler like Processor Sharing (PS), which splits the service capacity evenly among all present jobs.…”
Section: What Happens To Large Jobs?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while proportional fairness relates to the idea that it is fair for jobs to receive response times proportional to their service times, temporal fairness respects the seniority of customers and the first-come-first-serve policy. Wierman [46] provides an overview and comparison of various scheduling policies which are focused on guaranteeing equitable response times to all job sizes.…”
Section: Notion Of Fairness In Shared Environmentsmentioning
confidence: 99%
“…In [5], the notions of endogenous and exogenous unfairness are defined. In [6], algorithms are considered as fair if they do not favor jobs depending on their sizes. In [7], an algorithm is said to be fair iff it provides a response time that is less or equal than under PS for every task and any sample path.…”
Section: B Considering Resources Sharingmentioning
confidence: 99%